Metal-organic frameworks for advanced drug delivery - Siyu He; Li Wu; Xue Li; Hongyu Sun; Ting Xiong; Jie Liu; Chengxi Huang; Huipeng Xu; Huimin Sun; Weidong Chen; Ruxandra Gref; Jiwen Zhang (Elsevier, 2021)
Metal-organic frameworks (MOFs), comprised of organic ligands and metal ions/metal clusters via coordinative bonds are highly porous, crystalline materials. Their tunable porosity, chemical composition, size and shape, and easy surface functionalization make this large family more and more popular for drug delivery. There is a growing interest over the last decades in the design of engineered MOFs with controlled sizes for a variety of biomedical applications. This article presents an overall review and perspectives of MOFs-based drug delivery systems (DDSs), starting with the MOFs classification adapted for DDSs based on the types of constituting metals and ligands. Then, the synthesis and characterization of MOFs for DDSs are developed, followed by the drug loading strategies, applications, biopharmaceutics and quality control. Importantly, a variety of representative applications of MOFs are detailed from a point of view of applications in pharmaceutics, diseases therapy and advanced DDSs. In particular, the biopharmaceutics and quality control of MOFs-based DDSs are summarized with critical issues to be addressed. Finally, challenges in MOFs development for DDSs are discussed, such as biostability, biosafety, biopharmaceutics and nomenclature.